Analysis of Biomechanical Variables Based on the Imbalance of Ankle Muscle Strength in Ballet Dancers - Eun-kyo Chung; Seong-Hun Kim; Bee-Oh Lim (Korea Institute of Sport Science, 2023)
PURPOSE The purpose of this study is to analyze the biomechanical variables involved in ballet dancers' ankle muscle imbalance when performing relevé movements. METHODS The subjects of this study (n=14, age: 22.29±1.73 years old, height: 161.4±5.06cm, weight: 51.88±7.51kg) were 14 ballet dancers with 9 years of experience. Based on the reciprocal muscle strength ratio, the dancers were divided into the following groups: Close to the normal value (RMIS) and far from the normal value (RMIB) using the maximum values of plantar flexion and dorsiflexion of the ankle joint using an isokinetic measurement equipment (60°/sec). RMIB). The biomechanical variables, namely the ankle joint movement and ground reaction force, were subsequently measured. SPSS 26.0 was used for data analysis and independent t-test was used for statistical verification. RESULTS The ground reaction force in the Z (vertical) direction based on the ankle joint muscle strength imbalance of ballet dancers was significantly lower in the RMIB group. In addition, although it was not a statistically significant difference, the plantar flexion movement was lower in the RMIB group, and there was a significant difference in the generation of ankle joint movement in the Z direction. CONCLUSIONS In conclusion, in order for a ballet dancer to efficiently utilize the force generated from the supporting leg when performing a movement, ankle imbalance must be taken into consideration when training.